Knowledge, attitudes, and practices of parents toward sexuality education for primary school children in China - Zhang, Wenjing; Yuan, Yuzhi (Frontiers in Psychology, 2023)
This cross-sectional study provides insight into the perceptions of Chinese parents of primary school children with respect to sexuality education. A sample of 19,745 parents was surveyed using an online questionnaire in Beijing, Tianjin, and Hebei, China. SPSS version 23.0 was used for data analysis. In this study, nearly 90% of parents had positive attitudes toward the sexuality education of children in primary schools. However, Chinese parents had limited knowledge of sexuality education. More than 60% of parents were unaware of the sexuality questions that children may encounter at different ages and did not have any accurate information on child sexual abuse prevention education. Although 70% of parents (both fathers and mothers) reported that they had used television and Internet resources to talk with their children about sexuality and 63% reported that they had read books with their children about sexuality, < 30% reported using appropriate terminology with their children on sexuality education and only 40% reported talking to their children about sexuality comfortably. The multivariate linear regression equation showed some factors associated with the practices of parents in sexuality education, including parental knowledge, attitudes, their experience in receiving sex education in childhood, and their educational level. The findings from this study suggest that it is important to develop culturally relevant training programs for parents of primary schools in Chinese society. The implications and limitations of these findings are discussed.